Genetic and transcriptional analysis of inflammatory bowel disease-associated pathways in patients with GUCY2C-linked familial diarrhea. (2nd November 2018) - Tronstad, Rune R.; Polushina, Tatiana; Brattbakk, Hans-Richard; Stansberg, Christine; von Volkmann, Hilde Løland; Hanevik, Kurt; Ellinghaus, Eva; Jørgensen, Silje Fjellgård; Ersland, Kari Merete; Pham, Khanh D.-C.; Gilja, Odd Helge; Hovdenak, Nils; et al.
Abstract: Objective: Activating mutations in the GUCY2C gene, which encodes the epithelial receptor guanylate cyclase C, cause diarrhea due to increased loss of sodium chloride to the intestinal lumen. Patients with familial GUCY2C diarrhea syndrome (FGDS) are predisposed to inflammatory bowel disease (IBD). We investigated whether genes in the guanylate cyclase C pathway are enriched for association with IBD and reversely whether genetic or transcriptional changes associated with IBD are found in FGDS patients. Methods: ( 1) A set of 27 genes from the guanylate cyclase C pathway was tested for enrichment of association with IBD by Gene Set Enrichment Analysis, using genome-wide association summary statistics from 12, 882 IBD patients and 21, 770 controls. (2) We genotyped 163 known IBD risk loci and sequenced NOD2 in 22 patients with FGDS. Eight of them had concomitant Crohn's disease. (3) Global gene expression analysis was performed in ileal tissue from patients with FGDS, Crohn's disease and healthy individuals. Results: The guanylate cyclase C gene set showed a significant enrichment of association in IBD genome-wide association data. Risk variants in NOD2 were found in 7/8 FGDS patients with concomitant Crohn's disease and in 2/14 FDGS patients without Crohn's disease. In ileal tissue, downregulation of metallothioneins characterized FGDS patients compared to healthy controls. Conclusions: Our results support a role of guanylate cyclase C signaling and disturbed electrolyte homeostasis in development of IBD. Furthermore, downregulation of metallothioneins in the ileal mucosa of FGDS patients may contribute to IBD development, possibly alongside effects from NOD2 risk variants.